2021
DOI: 10.1111/ina.12820
|View full text |Cite
|
Sign up to set email alerts
|

Airborne particles and microorganisms in a dental clinic: Variability of indoor concentrations, impact of dental procedures, and personal exposure during everyday practice

Abstract: Studying air quality in healthcare facilities comprises of identification of the contaminant sources, their dispersion, and impact on indoor air. 1,2 Considering as ultimate purpose pathogen mitigation, minimization of the acquired infections both for the patients and the personnel is a challenging issue, 3,4 not only because of the direct contact with the contaminant sources but also due to their great variability in their characteristics and properties.Airborne particulate contaminants consist mainly of aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Carrying out aerosol/bioaerosol-generating procedures exposes the dentist and dental assistants to a larger number of aerosol and bioaerosol particles, which can facilitate the risk of infection with airborne diseases, such as COVID-19 [54]. Equipment such as ultrasonic scalers, handpieces, and dental air polishers emit aerosols of different sizes [55], meaning that the concentrations of bioaerosols can vary according to the type of treatment: higher during grinding and caries treatment, and lower during sealing and ultrasonic scaling [54]. After dental procedures, spray contamination may extend to up to 36 inches, with high levels at up to 12 inches, and persist for 30 min after the AGP [56].…”
Section: Discussionmentioning
confidence: 99%
“…Carrying out aerosol/bioaerosol-generating procedures exposes the dentist and dental assistants to a larger number of aerosol and bioaerosol particles, which can facilitate the risk of infection with airborne diseases, such as COVID-19 [54]. Equipment such as ultrasonic scalers, handpieces, and dental air polishers emit aerosols of different sizes [55], meaning that the concentrations of bioaerosols can vary according to the type of treatment: higher during grinding and caries treatment, and lower during sealing and ultrasonic scaling [54]. After dental procedures, spray contamination may extend to up to 36 inches, with high levels at up to 12 inches, and persist for 30 min after the AGP [56].…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols containing microorganisms are called bioaerosols [ 27 , 28 ]. The microorganisms mainly originate from patient-related sources such as biofilm, calculus, blood, saliva, and the nasopharynx [ 29 , 30 ]. Therefore, high concentrations of streptococci [ 30 ], staphylococci [ 31 ], and propionibacteria, being part of the natural microflora of skin and oral cavity, are also detected during treatment [ 32 – 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contaminated water pipes can pose a serious risk to immune-compromised patients, but also to dental staff, as the microorganisms present can be very diverse and potentially pathogenic [ 36 ]. Furthermore, potentially pathogenic microorganisms can often be isolated [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sotiriou et al [ 21 ] reported that most aerosols were below 0.5 μm by using the portable particle counter (Model CI550, Climet Instrument Co., Redlands, CA, USA) to continuously measure aerosol concentrations under drilling dental treatment for five working days. Research has shown that fine particles are more infectious [ 22 ] and may contain heavy metals [ 23 ], as well as pathogenic microorganisms [ 24 ], as they are small enough to penetrate the alveolar area of the body and enter the bloodstream [ 25 , 26 ]. Fine particles can be suspended in air for a long time and over long distances [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%